Abundantly more : the theological promise of the arts in a reductionist world - Begbie, Jeremy (Grand Rapids, MI. Baker Academic, 2023)
"In a culture that so often seems to shrink and flatten our vision, reducing the world to mere atoms and us to mere things, the arts can break our imaginations open. A world-renowned theologian helps us see this world and ourselves as infinitely more than we could ever imagine: as created and redeemed by the inexhaustible love of God"--
Includes bibliographical references and index
Keywords: Christianity and the arts; Arts and religion